2019
DOI: 10.1142/s2424835519500516
|View full text |Cite
|
Sign up to set email alerts
|

Flexor Subzone II A–D Range of Motion Progression during Healing on a No-Splint, No-Tenodesis Protection, Immediate Full Composite Extension Regimen

Abstract: Background: The objective was to study the hypotheses that an advanced zone II flexor tendon rehabilitation protocol would avoid rupture, achieve a high range of excursion, and minimize interphalangeal contracture during both the early phases and at the conclusion of healing. We also proposed the null hypothesis of no difference between any two of the zone II subdivisions. Methods: Fifty-one consecutive adult patients with zone II flexor tendon repairs of a single finger were retrospectively evaluated on an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The available range of motion also differed depending on the splint position, as discussed above. None of the guidelines advocated full active composite extension of the MCPJs and IPJs within the first 4 weeks of surgery, as prescribed in the study by Henry et al 33 Across the identified guidelines, the greatest range of finger movement was available with the RMF splint and short DBS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The available range of motion also differed depending on the splint position, as discussed above. None of the guidelines advocated full active composite extension of the MCPJs and IPJs within the first 4 weeks of surgery, as prescribed in the study by Henry et al 33 Across the identified guidelines, the greatest range of finger movement was available with the RMF splint and short DBS.…”
Section: Discussionmentioning
confidence: 99%
“…Future advances in flexor tendon rehabilitation may dispense with full-time splint use altogether. Henry et al reported a retrospective case series of 51 flexor tendon patients when a splint was used ‘as a defensive shield only in particularly dangerous environments (p407)’ 33 . The splint was positioned in wrist extension and MCPJ flexion, although joint angles were not reported.…”
Section: Discussionmentioning
confidence: 99%